Aspek Hukum Penolakan Protokol Kesehatan di Era Pandemi COVID-19 - Mahesa Paranadipa Maikel (Jurnal MHKI, 2021)
Informed consent can be a form of communication between doctors and patients or the patient's family. Apart from Informed consent, there are also other patient statements, namely "Refusal of Medical Action" or "Informed Refusal". In the COVID-19 pandemic situation, patients and families often reject procedures in health facilities. Article 56 of Law Number 36 of 2009 concerning Health states that a person does not have the right to accept or reject part or all of the assistance measures given to him/her for sufferers of a disease whose disease can quickly spread to the broader community. Refusal of health protocols in a pandemic situation can potentially result in criminal sanctions in some laws and the Criminal Code.